(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Thromboangiitis Obliterans or Buerger Disease is a non-atherosclerotic obstructive syndrome of small to medium arteries of the upper and lower extremities that causes blockage, recurrent and progressive inflammation, and clotting of the walls of the arteries. It becomes. This disease is usually associated with the use of tobacco derivatives, especially smoking, but it is also associated with the consumption of smokeless tobacco. Method: 108 healthy smokers and non-smokers who participated in the recall of Buerger’s disease were studied and clinical information on smoking and drug use was entered in the relevant forms. Patients' informed consent was obtained to participate in research and experiments on their blood samples. 10 cc of blood was taken from each patient and serum was isolated and used for relevant tests. ELISA method was used to measure the concentration of cytokines IL-6 and TNF-α. After data collection, SPSS software version 24 was used for data analysis. Results: The mean age of Buerger patients in the present study was 49.67± 8.91 years. The most common clinical variables during the study, the results showed that in smokers there are significant changes in serum IL-6 levels compared to non-smokers (p <0.05). Conclusion: Considering the significant relationship between immune system components and some clinical symptoms and the role of their abnormal function in Buerger disease, they can a criterion for determining the course of Buerger disease or based on them, treatment strategy determined.